The analysis of tissue culture and spawn preparation of edible mushroom (Pleurotus Ostreatus) in Malaysia - Pavithra, Maniam (2025)
Pleurotus ostreatus is commonly known as the oyster mushroom, and has a great nutritional and medicinal value. It is the second most commercially cultivated in the world as the demand is increasing day by day. Due to conflicting reports, this study evaluated the impact of several grains, such as sorghum, wheat, and barley, as a spawn preparation. The main objectives of this study were to analyze the cultivation of Pleurotus ostreatus using tissue culture technique, effect different grains and to analyze the quality of Pleurotus ostreatus on optimized grain. One control and duplicates of Pleurotus ostreatus were performed during the tissue culture. After 10 days of incubation, the plate displays a white to beige colour colony with a fluffy or cotton-like texture. A healthy colonisation had a total diameter of 84 mm. By proceeding grain inoculation with healthy mycelium, the effect and colonization rate was determined. There were no signs of mycelium contamination, and the mycelium looks dense, fluffy, and healthy which are excellent signs. According to the colonisation rate, sorghum was the most effective grain for preparing spawn, followed by barley and wheat. They took 17, 19, and 20 days, respectively to fully colonize. Following analyzing the quality of Pleurotus ostreatus on sorghum, it was discovered that the walls of the hyphae, which are clear, long, thread- like structures, were consistently smooth. Cross walls separated the septate hyphae into compartments. There was also no contamination found.